2020
DOI: 10.3390/molecules25112648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Preparation Procedure on the Performance of the Microporous HKUST-1 Metal-Organic Framework in the Liquid-Phase Separation of Aromatic Compounds

Abstract: To date, metal-organic frameworks (MOFs) have been recognized as promising solid phases in high-performance liquid chromatography (HPLC). This research aimed to elucidate the role of the physico-chemical characteristics of the microporous HKUST-1 metal-organic framework in its operation as a selective adsorbent in HPLC. For this, the HKUST-1 samples were prepared by microwave-assisted synthesis and a solvothermal procedure. According to the chromatographic examinations, the HKUST-1 material synthesized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…It can be seen from Figure 6 that the HKUST-1 reference sample has micropores with a narrow size distribution in the 0.6 to 0.9 nm region. It is in a good accordance with the micropore diameter reported for the pristine HKUST-1 metal-organic framework [ 56 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It can be seen from Figure 6 that the HKUST-1 reference sample has micropores with a narrow size distribution in the 0.6 to 0.9 nm region. It is in a good accordance with the micropore diameter reported for the pristine HKUST-1 metal-organic framework [ 56 ].…”
Section: Resultssupporting
confidence: 89%
“…Probably, the observed pattern is induced because of the abundant presence of micropores in the HKUST-1 structure ( Table 1 ) and, consequently, by diffusion difficulties during the adsorbate mass transfer in these pores upon the dynamic process of HPLC. Recently [ 56 ], we suggested that the adsorbate molecules cannot penetrate into HKUST-1 micropores under the high mobile phase flow rates because of diffusion limitations, while they can do under the low mobile phase flow rates. Therefore, no adsorption equilibrium during the pristine HKUST-1 powder exploitation as a stationary phase in HPLC, in our opinion, signifies the necessity of improving the surface chemistry and, especially, chromatographic properties of this matrix through enhancing its porous structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the context of the efficient control of the morphology of MOF crystallites, MW-assisted synthesis shows particular potential. This technique is recognized as a promising strategy to efficiently manipulate the key physico-chemical characteristics of produced MOF materials [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the impact of MW-assisted synthesis in the H 2 O-DMF system at an atmospheric pressure using a household MW oven on the structural, compositional, morphological and textural characteristics of the produced HKUST-1 material and thereby on its performance in liquid phase adsorption [32].…”
Section: Introductionmentioning
confidence: 99%